Exploring EFL Students’ Perception of Online Learning via Microsoft Teams: University Level in Indonesia - Ahmad Ridho Rojabi (Universitas Ahmad Dahlan, 2020)
An internet connection has been crucial in the era of globalization to enhance human activities in various activities of economic, culture, defense, and many others, especially in the EFL classroom setting. Microsoft Teams as an innovative online learning platform provides unique features to enhance its potential to help EFL teachers to conduct better interaction as well learning environment in online learning. This research aimed at exploring students’ perceptions of online learning via Microsoft Teams. The study was conducted with twenty-eight sixth-semester students at Open University (Universitas Terbuka-UPBJJ Jember). Data were collected by using questionnaires to gain information about the EFL students’ perception of online learning via Microsoft Teams. The questionnaire was distributed to the students through Google forms after all materials in online learning had been conducted. The questionnaires data obtained were analyzed descriptively. The finding of the research revealed that online learning via Microsoft Teams is categorized as something new for the students but this interaction and learning environment motivated students in participating online learning, as a result, they can easier to comprehend the learning materials.